PERLINDUNGAN HUKUM TERHADAP PEKERJA KEBERSIHAN MELALUI BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI DINAS LINGKUNGAN HIDUP KABUPATEN TABANAN - Putu Milania Riska Purnami; Lis Julianti (Jurnal Hukum Mahasiswa, 2021)
Manpower as an important element in a company requires protection, maintenance and security in carrying out its work. The protection of workers still has to be improved, including improving working conditions, improving welfare and implementing work safety and welfare that is integrated with all workforce development programs accompanied by law enforcement efforts. The Environment Office Tabanan Regency did not register its workers because of existing regulations, in addition to the insufficient budget for The Social Security Administration Agency payments. The inhibiting factor in the implementation of legal protection for workers in the Tabanan Regency The Environment Office was internal factors regarding legal awareness of workers not knowing about the Legislation, external factors, namely not the existence of supervision and guidance on entrepreneurs and workers by the Manpower Office so that the implementation of legal protection does not run in accordance with the statutory regulations.